Mansfield’s short story from Woolf’s modernist view - Gomes, Carlos Magno (2015)
This paper pays a tribute to the narrative technique of Katherine Mansfield, through the study on the spatiotemporal fragmentation present in the short story Bliss. Her creation process highlights marks of the story of atmosphere and the temporal fragmentation of the narrative. It is possible to observe that the text is based upon the spatiotemporal displacement of the protagonist in a futile and conservative London society. Theoretically, this work explores the intertextuality perspectives of the modernist narrative according to Virginia Woolf. About the spatiotemporal displacement, it goes through the concepts of space and heterotopia by Gaston Bachelard and Michel Foucault.